Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2014
DOI: 10.1145/2556288.2557255
|View full text |Cite
|
Sign up to set email alerts
|

The routines and needs of grandparents and parents for grandparent-grandchild conversations over distance

Abstract: A variety of systems have been designed to support communication between distance-separated grandparents and grandchildren. Yet there are few studies of the actual conversational routines of these groups as well as the social challenges that might arise as a result of technology usage. To address this gap, we conducted an interview and diary study that explores the conversational practices of distanceseparated grandparents and young grandchildren (aged 3-10) from the perspective of the grandparents and parents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 32 publications
2
26
0
1
Order By: Relevance
“…Participants may not adhere to the study expectations (e.g., retroactively filling in data shortly before a study session, known as "parking lot compliance" [23]) which can impact the reliability of the data.. There is room for a variety of media in diary studies, such as text, photos, audio, and video (e.g., [1,5,8,12]) captured using a range of tools like paper, online forms, mobile phones, or cameras (e.g., [1,12,16,34]). In our ARC method, we use the data collection phase of the diary study as an individual activity, but have participants share their logs with each other and discuss them.…”
Section: Overviewof Hciresearch Methodsmentioning
confidence: 99%
“…Participants may not adhere to the study expectations (e.g., retroactively filling in data shortly before a study session, known as "parking lot compliance" [23]) which can impact the reliability of the data.. There is room for a variety of media in diary studies, such as text, photos, audio, and video (e.g., [1,5,8,12]) captured using a range of tools like paper, online forms, mobile phones, or cameras (e.g., [1,12,16,34]). In our ARC method, we use the data collection phase of the diary study as an individual activity, but have participants share their logs with each other and discuss them.…”
Section: Overviewof Hciresearch Methodsmentioning
confidence: 99%
“…As Harley and colleagues (2012) suggest, the motivation to learn to use new computer-based technologies increases in the case of remote grandparents who are forced to build a relationship with their grandchildren over great geographic distance. Grandparents eventually react to social media opportunities which respond to their need to play (Raffle et al, 2010) and to get emotionally involved with their families and social networks (Breheny, Stephens, & Spilsbury, 2013;Forghani, & Neustaedter, 2014).…”
Section: Grandparents' Use Of Icts To Communicate With Grandchildrenmentioning
confidence: 99%
“…Forghani and Neustaedter [4], studying the communication patterns of distance-separated grandparents and grandchildren, identified that adult children usually assume the role of family communication broker in intergenerational exchanges, thus providing the means to share information between people that do not have frequent contact. Similarly, Gutierrez and Ochoa [5] identified that adult children -and sometimes grandmothers-also assume a similar role aiming to provide indirect communication means as a way to sustain the affective link among loosely coupled people.…”
Section: Related Workmentioning
confidence: 99%